Graphitic Carbon Nitride Nanomaterials-Based Electrochemical Sensing Interfaces for Monitoring Heavy Metal Ions in Aqueous Environments - Cheng Yin; Yao Liu; Tingting Hu; Xing Chen (Nanomaterials)
The persistent threat of heavy metal ions (e.g., Pb2+, Hg2+, Cd2+) in aqueous environments to human health underscores an urgent need for advanced sensing platforms capable of rapid and precise pollutant monitoring. Graphitic carbon nitride (g-C3N4), a metal-free polymeric semiconductor, has emerged as a revolutionary material for constructing next-generation environmental sensors due to its exceptional physicochemical properties, including tunable electronic structure, high chemical/thermal stability, large surface area, and unique optical characteristics. This review systematically explores the integration of g-C3N4 with functional nanomaterials (e.g., metal nanoparticles, metal oxide nanomaterials, carbonaceous materials, and conduction polymer) to engineer high-performance sensing interfaces for heavy metal detection. The structure-property relationship is critically analyzed, emphasizing how morphology engineering (nanofibers, nanosheets, and mesoporous) and surface functionalization strategies enhance sensitivity and selectivity. Advanced detection mechanisms are elucidated, including electrochemical signal amplification, and photoinduced electron transfer processes enabled by g-C3N4’s tailored bandgap and surface active sites. Furthermore, this review addresses challenges in real-world deployment, such as scalable nanomaterial synthesis, matrix interference mitigation, and long-term reliable detection. This work provides valuable insights for advancing g-C3N4-based electrochemical sensing technologies toward sustainable environmental monitoring and intelligent pollution control systems.